2015
DOI: 10.3109/14992027.2015.1059502
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the performance of two binaural beamformers in complex and dynamic multitalker environments

Abstract: Objective Binaural beamformers are super-directional hearing aids created by combining microphone outputs from each side of the head. While they offer substantial improvements in SNR over conventional directional hearing aids, the benefits (and possible limitations) of these devices in realistic, complex listening situations have not yet been fully explored. In this study we evaluated the performance of two experimental binaural beamformers. Design Testing was carried out using a horizontal loudspeaker array… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 22 publications
3
42
1
Order By: Relevance
“…Most probably, the listeners could not localize the sound source optimally, as their face was not turned towards it, leaving the target source outside the spot of the beamformer. These results are comparable with the study of Best et al [2015], who also found reduced SNR for dynamic speech targets. In Picou et al [2014], a deterioration in localization ability was found.…”
Section: Discussionsupporting
confidence: 82%
“…Most probably, the listeners could not localize the sound source optimally, as their face was not turned towards it, leaving the target source outside the spot of the beamformer. These results are comparable with the study of Best et al [2015], who also found reduced SNR for dynamic speech targets. In Picou et al [2014], a deterioration in localization ability was found.…”
Section: Discussionsupporting
confidence: 82%
“…Finally, one of the practical goals of this work is to provide new tools for predicting the real-world benefit of hearing aids and their processing schemes. Spatially dynamic listening environments are of particular importance for the assessment of devices that incorporate directional (and more recently, superdirectional) processing (e.g., see Picou et al, 2014;Best et al, 2015). In these situations it is possible for a listener to move their head, or for a directional beam to automatically track the target sound, such that the relevant signal is always in the focus of the directional beam.…”
Section: Discussionmentioning
confidence: 99%
“…These schemes were chosen since, due to their directional processing, they were expected to be highly sensitive to any potential artifacts created by the two VSEs (Oreinos and Buchholz, 2015). Similar to the study by Best, Mejia, et al (2015), two different listening tests were conducted to measure the performance of the CRD as well as the additional benefit provided by the BBF processing: a speech intelligibility test and an acceptable noise level (ANL) test. The difference in performance measured between the two VSEs and the real (reference) environment provided a measure of the accuracy of the two VSEs and, thus, allowed conclusions on the applicability of the two VSEs for testing (directional) HAs.…”
mentioning
confidence: 99%